2019
DOI: 10.1002/jcla.22943
|View full text |Cite
|
Sign up to set email alerts
|

Identification and diagnostic value of pleural fluid periostin and serum periostin of malignant pleural effusions in patients with non–small‐cell lung cancer

Abstract: BackgroundLimited data are available for the diagnostic value, and the diagnostic sensitivity and specificity of pleural fluid periostin (pPOSTN) and serum periostin (sPOSTN) in malignant pleural effusion (MPE) caused by non–small‐cell lung cancer (NSCLC).MethodsWe collected 84 pleural effusion samples, including 44 cases of MPE caused by NSCLC and 40 cases of benign pleural effusions (BPEs) from August 2018 to January 2019. The pPOSTN, sPOSTN, pleural fluid lactate dehydrogenase (pLDH), pleural effusion adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Therefore, the combined detection of PE POSTN, CEA, and CR can improve the diagnostic accuracy of lung cancer‐related MPE. While Wang et al reported the diagnostic value of PE POSTN in MPE associated with NSCLC, 47 there are some innovations in our study. First, our study included patients with MPE associated with both NSCLC and SCLC.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, the combined detection of PE POSTN, CEA, and CR can improve the diagnostic accuracy of lung cancer‐related MPE. While Wang et al reported the diagnostic value of PE POSTN in MPE associated with NSCLC, 47 there are some innovations in our study. First, our study included patients with MPE associated with both NSCLC and SCLC.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, periostin is an extracellular protein and should be accessible via air-way fluid as well as other extracellular fluid. Recent studies have also demonstrated that the expression of periostin can be detected in the pleural effusions of NSCLC patients (53).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with lymphoma patients experience multiorgan and tissue damage, leading to elevated LDH levels in the peripheral blood. In contrast, patients with lung cancer typically exhibit increased LDH levels in pleural effusion ( Wang et al, 2019 ). We defined persistent fever as fever symptoms lasting for >10 days.…”
Section: Discussionmentioning
confidence: 99%